Outcomes of feeding activity of the sea cucumber Holothuria tubulosa on quantity, biochemical composition, and nutritional quality of sedimentary organic matter - Pasquini, Viviana; Addis, Pierantonio; Giglioli, Ambra Angelica; Moccia, Davide; Pusceddu, Antonio (Frontiers in Marine Science, 2023)
Introduction Holothuria tubulosa is one of the most common sea cucumbers in the Mediterranean Sea, generally associated with organically enriched coastal sediments and seagrass beds. As a deposit-feeder, it is responsible for strong bioturbation processes and plays a putative key role in sedimentary carbon cycling and benthic trophodynamics. With the aim of exploring the potential use of holothuroids as a tool for remediating eutrophicated sediments, we investigated the effects of H. tubulosa on sedimentary organic matter quantity, biochemical composition, and nutritional quality. Methods Holothuroids and associated samples of ambient sediments were collected in two sites located in the Central-Western Mediterranean Sea (Sardinia, Italy) and characterized by different trophic status backgrounds: the site of Oristano characterized by sandy-muddy sediments and the presence of mariculture plants (ranked as meso-eutrophic) and the site of Teulada characterized by sandy sediments and Posidonia oceanica meadows (ranked as oligo-mesotrophic). We compared the biochemical composition (proteins, carbohydrates, lipids) of ambient sediment vs sea cucumbers feces and the sedimentary protein content vs protein content in the sediments retrieved in different gut sections (esophagus, mid gut, end gut) of the holothuroid. Results Our results reveal that holothuroids feeding on meso-eutrophic sediments can increase protein (1.5 times) and lipid (1.3 times) content through their defecation, thus making these substrates a more labile food source for other benthic organisms. We report here that H. tubulosa feeding on meso-eutrophic sediment is most likely able to actively select particles rich in labile organic matter with buccal tentacles, as revealed by the protein content in the esophagus that is up to 2-folds higher than that in the source sediment. According to the inverse relationship between assimilation rates and availability of organic substrates and the optimal foraging theory, H. tubulosa feeding on oligo-mesotrophic sediments showed potential assimilation of proteins ca. 25% higher than that of specimens feeding on meso-eutrophic sediments. Discussion Our results reveal that H. tubulosa feeding on meso-eutrophic sediments can profoundly influence the benthic trophic status, specifically modifying the biochemical composition and nutritional quality of organic matter, thus paving the way to its possible use in bioremediation actions of eutrophicated sediments and in Integrated Multi-Trophic Aquaculture systems.